Flood Inoculation of Fusarium eumartii in Tomato Seedlings: Method for Evaluating the Infectivity of Pathogen Spores - María Terrile; Florencia Mesas; María Picco; María Salcedo; Andrea Mansilla (Bio-Protocol)
The Fusarium genus includes various fungi of great significance in agriculture. Fusarium solani f. sp. eumartii (F. eumartii), traditionally known as a potato pathogen, has also been identified as a cause of disease in tomatoes. This protocol provides a detailed, efficient, and robust flood-inoculation method for assessing F. eumartii infection of young tomato seedlings grown on MS medium plates. It includes the evaluation of the lesion area and the quantification of the remaining fungal inoculum in tomato seedlings. In summary, the straightforwardness and efficiency of this bioassay make it a powerful quantitative tool for selecting fungicidal compounds or defense response inducers in tomato plants, offering a promising approach with significant potential for preventing fungal diseases in crops.